Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) = -15x4y7 - (-10x5y6) - (-5x3y5)
= -15x4y7 + 10x5y6 + 5x3y5
\(\left(x-2\right)\left(x^2-2x+1\right)\left(x+2\right)\left(x^2+2x+4\right)\)
\(=\left[\left(x-2\right)\left(x^2+2x+4\right)\right]\left[\left(x+2\right)\left(x^2-2x+4\right)\right]\)
\(=\left(x^3-8\right)\left(x^3+8\right)\)
\(=x^6-64\)
\(\left(x-2\right)\left(x^2-2x+4\right)\left(x+2\right)\left(x^2+2x+4\right)\)
\(=\left(x-2\right)\left(x^2+2x+4\right)\left(x+2\right)\left(x^2-2x+4\right)\)
\(=\left(x^3-8\right)\left(x^3+8\right)\)
\(=x^6+64\)
[(x2-2xy+2xy2).(x+2y)-(x2+4y2).(x-y)]2xy
=( x3 + 2x2y-2x2y-4xy2+2x2y2+4xy3-x3+x2y-4xy2+4y3 )2xy
=2xy(2x2y2-8xy2+4xy3+x2y+4y3)
= 4x3y3-16x2y3+8x2y4+2x3y2+8xy4
Trả lời:
[ ( x2 - 2xy + 2xy2 ) ( x + 2y ) - ( x2 + 4y2 ) ( x - y ) ] 2xy
= [ ( x3 + 2x2y - 2x2y - 4xy2 + 2x2y2 + 4xy3 ) - ( x3 - x2y + 4xy2 - 4y3 ) ] 2xy
= ( x3 + 2x2y - 2x2y - 4xy2 + 2x2y2 + 4xy3 - x3 + x2y - 4xy2 + 4y3 ) 2xy
= ( x2y - 8xy2 + 2x2y2 + 4xy3 + 4y3 ) 2xy
= 2x3y2 - 16x2y3 + 4x3y3 + 8x2y4 + 8xy4
1.
$2x^3-21x^2+67x-60=2x^2(x-5)-11x(x-5)+12(x-5)$
$=(x-5)(2x^2-11x+12)$
$\Rightarrow (2x^3-21x^2+67x-60):(x-5)=2x^2-11x+12$
2.
$x^4+2x^3+x-25=x^2(x^2+5)+2x(x^2+5)-5x^2-9x-25$
$=x^2(x^2+5)+2x(x^2+5)-5(x^2+5)-9x=(x^2+5)(x^2+2x-5)-9x$
$\Rightarrow (x^4+2x^3+x-25):(x^2+5)=x^2+2x-5$ và dư $-9x$
\(=\left(x^2-4\right)\left(x^2+4\right)=x^4-16\)
(x – 2)(x + 2)(x2 + 4)
=(\(x^2\)-4)(\(x^2\)+4)
=\(x^4\)-16
Mik gửi ạ
@ann1234